2019
DOI: 10.1002/cmdc.201900576
|View full text |Cite
|
Sign up to set email alerts
|

Dual Farnesoid X Receptor/Soluble Epoxide Hydrolase Modulators Derived from Zafirlukast

Abstract: The nuclear farnesoid X receptor (FXR) and the enzyme soluble epoxide hydrolase (sEH) are validated molecular targets to treat metabolic disorders such as non‐alcoholic steatohepatitis (NASH). Their simultaneous modulation in vivo has demonstrated a triad of anti‐NASH effects and thus may generate synergistic efficacy. Here we report dual FXR activators/sEH inhibitors derived from the anti‐asthma drug Zafirlukast. Systematic structural optimization of the scaffold has produced favorable dual potency on FXR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Recently, dual FXR activators/sEH inhibitors have been reported that are derived from the antiasthma drug Zafirlukast. These inhibitors possess favorable dual potency towards FXR and sEH while reducing the original cysteinyl leukotriene receptor antagonism of the lead drug [ 148 ]. Inceoglu and coworkers demonstrated that coadministration of phosphodiesterase 4 (PDE4) and sEH inhibitors results in an enhanced analgesic effect compared to the individual treatments [ 149 ].…”
Section: Dual Inhibition/modulation Of Seh As Part Of Anti-inflammmentioning
confidence: 99%
“…Recently, dual FXR activators/sEH inhibitors have been reported that are derived from the antiasthma drug Zafirlukast. These inhibitors possess favorable dual potency towards FXR and sEH while reducing the original cysteinyl leukotriene receptor antagonism of the lead drug [ 148 ]. Inceoglu and coworkers demonstrated that coadministration of phosphodiesterase 4 (PDE4) and sEH inhibitors results in an enhanced analgesic effect compared to the individual treatments [ 149 ].…”
Section: Dual Inhibition/modulation Of Seh As Part Of Anti-inflammmentioning
confidence: 99%
“…Zafirlukast: Schierle et al, in their study, derive a compound from zafirlukast that has the ability to interact with farnesoid X receptor and soluble epoxide hydrolase (FXRA/sEHi). The combination of which can prove to be a potential therapeutic target in the treatment of metabolic syndrome and NASH [ 22 ]. The farnesoid X receptor when activated has the ability to decrease hepatic steatosis and fibrosis which has been implicated in the development of NASH as one of the key pathological changes.…”
Section: Reviewmentioning
confidence: 99%
“…The farnesoid X receptor when activated has the ability to decrease hepatic steatosis and fibrosis which has been implicated in the development of NASH as one of the key pathological changes. This activity of NASH is brought about by Zafirlukast-derived FXRA/sEHi 13 and 16 [ 22 ]. The sEH in turn has exhibited a strong anti-inflammatory effect which can be the turning point in the treatment of NASH.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Designed polypharmacology addressing complementary pathomechanisms may, therefore, offer access to synergistic efficacy in this complex disease. Following this strategy, we have previously developed dual modulators to target, for example, farnesoid X receptor (FXR) and soluble epoxide hydrolase (sEH),[ 6 , 7 , 8 ] or FXR and peroxisome proliferator‐activated receptors (PPARs). [ 9 , 10 ] Strong therapeutic efficacy of such multi‐target agents in preclinical NASH models[ 10 , 11 ] corroborates the potential of designed polypharmacology in this indication.…”
Section: Introductionmentioning
confidence: 99%